Effect of geometrical features of fillers particles on viscosity of polyethylene or polystyrene in melt - Stabik, J. (Polimery, 2022)
General dependence concerning viscosity of dispersive systems has been described. The effect of geometrical features of fillers' particles on viscosity of filled polymers was presented in details. Own results of investigations of viscosity of low-density polyethylene or polystyrene filled with various mineral fillers, differing in chemical character and particles' forms were presented (Table 1 and 2). Empirical models (correlation functions) relating the fillers' geometrical features with compound viscosity (Table 3, Figs. 1-4) were elaborated. For both polymers investigated similar dependence showing similar statistical characteristics has been obtained. Aspect ratio of filler particle influenced most the viscosity of composition investigated. Specific surface showed less influence and the particle diameter - the least of all.